2014
DOI: 10.1111/hdi.12164
|View full text |Cite
|
Sign up to set email alerts
|

A minimally painful, comfortable, and safe technique for hemodialysis catheter placement in children: Superficial cervical plexus block

Abstract: The superficial cervical plexus block (SCPB) is utilized in pediatric patients to perform certain surgical procedures, but there is no evidence supporting its use in hemodialysis catheter placement. We evaluated the analgesic effectiveness, intraoperative complications, and patient satisfaction associated with SCPB for pediatric patients in renal failure undergoing emergent dialysis catheterization. A total of 52 patients ranging from 1 to 17 years old that required emergent dialysis catheter placement and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…They form the sensory fibers of these regions [1820] (Figures 7(a)–7(b) show the domain of the plexus) (Figure 7). Çiftci et al [19] reported that when SCPB was used prior to the insertion of a hemodialysis catheter into either IJV or SV, patients had low pain scores during the procedure and the block was successful and did not require additional sedoanalgesia in any patient. Ben Ho et al [20] reported that they performed SCPB in the cervical fractures, paracervical muscle spasm, acromioclavicular joint injuries, and rotator cuff disorders in the emergency department and obtained significant analgesic results.…”
Section: Discussionmentioning
confidence: 99%
“…They form the sensory fibers of these regions [1820] (Figures 7(a)–7(b) show the domain of the plexus) (Figure 7). Çiftci et al [19] reported that when SCPB was used prior to the insertion of a hemodialysis catheter into either IJV or SV, patients had low pain scores during the procedure and the block was successful and did not require additional sedoanalgesia in any patient. Ben Ho et al [20] reported that they performed SCPB in the cervical fractures, paracervical muscle spasm, acromioclavicular joint injuries, and rotator cuff disorders in the emergency department and obtained significant analgesic results.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided superficial cervical plexus blocks are found to be successful for treating pain in emergency care settings [ 9 ]. Superficial cervical plexus blocks can also be used to provide surgical anesthesia for lymph node biopsy and excision of a thyroid nodule and placement of hemodialysis catheters [ 20 , 21 ]. Ultrasound-guided bilateral cervical plexus blocks could be performed for postoperative analgesia following thyroid surgeries [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Superficial cervical plexus block (SCPB) has been described for tunneled central venous catheters (CVCs) in awake patients, 1 hemodialysis catheter placement in pediatric patients, 2 and awake invasive neck surgeries including carotid endarterectomy 3 and thyroidectomy. 4 To our knowledge, there have been no reports of the use of SCPB in obstetric patients to facilitate central line placement.…”
mentioning
confidence: 99%